Commentary: How Bayes factors change scientific practice - Perezgonzalez JD (Frontiers Media)
Dienes's (2016) article is one of the contributions to the special issue “Bayes factors for testing hypotheses in psychological research…” being published by the Journal of Mathematical Psychology. One concern I have with Dienes's article is its “one-size-fits-all” philosophy. A second concern is the reification of Bayes factors as the solution to the credibility crisis. I find it naive that a single approach is still proposed as the one and only tool for testing data. I also find it naive to assume that Bayes factors, with no clear replicability mechanism attached to them, are the ones to resolve the credibility crisis in psychology.
Keywords: Bayes factors; significance testing; acceptance testing; meta-analysis; replication; Fisher; Neyman-Pearson; Jeffreys; 1701 Psychology; 1702 Cognitive Sciences